Political institutions under dictatorship - Gandhi, Jennifer 1975- (Cambridge Univ. Press, 2008)
The world of dictatorial institutions -- Three illustrative cases : Kuwait, Morocco, Ecuador -- The use of institutions to coopt -- Institutions and policies under dictatorship -- Institutions and outcomes under dictatorship -- Institutions and the survival of dictators -- Conclusion -- Codebook of variables